PERAN PERAWAT PUSKESMAS SEBAGAI PENDIDIK DALAM MENJALANKAN PROGRAM GERAKAN MASYARAKAT HIDUP SEHAT (GERMAS) - Suci Amalia Amri; Ari Pristiana Dewi; Sofiana Nurchayati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2019)
Germas or the movement of a healthy living community is a systematic and planned action carried out jointly by the community with awareness, willingness and ability to behave in a healthy manner to improve the quality of life. The implementation of Germas must be carried out by all levels of society, across community organizations, and the community, to jointly contribute to realize a healthier Indonesian society. Puskesmas nurses in running the Germas program as educators are carried out through health promotion actions and role models. This study uses a cross sectional approach with a sample of 71 nurses taken using a cluster sampling technique. Data analysis using univariate analysis. The results obtained by the role of nurses in running the Germas program played a good role as educators as much as 52.1%. It is recommended that puskesmas nurses play an active role in the implementation of Germas by increasing Germas' promotional activities. Keywords: Educators, Germas, Puskesmas, Role of nurses